The similarity of metaphorical concepts in Hassan Al-Bassam’s poetry and its impact on the pictorial system - Jawed, . Dr. Adel Abdel-Kazem (Thi Qar Arts Journal, 2023)
Metaphor occupies a significant space in the Arab and Western rhetorical and critical field. On the one hand, it is an aesthetic stylistic feature concerned with embellishing and improving discourse. The metaphor has spread in the poetry of our poet in such a way that it allows us to count it as an artistic feature that enters the number of pictorial features that are no less important than analogy, so he multiplies it in praising him and lamenting him. , and creativity. The poet has relied a lot on metaphor in forming his poetic images, and gives them novelty, vitality and diversity by reformulating relationships in new forms, in addition to the symbol that conveys the poet’s experience and suffering honestly and purely, when the symbol expresses the word and the general concept in the poem the deep meaning that he wants The poet has performed his role to the fullest, so the interaction takes place between the text and the recipient, and intentionality is the focus of this interaction, as it proceeds from the text to the recipient, and from the recipient to the text, and that the metaphorical style has embodied a hidden relationship between two different poles, and the greater the distance between these two poles Emerged with the effectiveness of metaphor.